THE ACTIVITIES OF NIO, COO AND FEO IN SILICATE MELTS - Holzheid A.; Palme H.; Chakraborty S. (My University, 1997)
Solubilities of NiO, Coo and FeO in silicate melts have been determined experimentally as a function of temperature, oxidation state and melt composition. The results -show that Fe, Ni and Co are dissolved as divalent cations in silicate melts at oxygen fugacities varying from IW + 1.5 to IW − 3. The well defined valence state of these elements in the melt allows the calculation of activity coefficients. The activity coefficients of FeO, NiO and Coo in the silicate melt, calculated by assuming oxides as melt components, were found to be independent of oxygen fugacity and of temperature within a temperature range of 1300°C to 1600°C. Earlier reports on temperature-dependent NiO activity coefficients were based on a standard state for NiO in the melt of solid NiO. When the more appropriate liquid standard state is used, the temperature dependence disappears. The activity coefficients were not affected by variations in FeO (from 0 to 12 wt.%) and MgO (from 4 to 30 wt.%) contents, except for a small increase of γcoo and γ“Feo” at MgO-contents above 20 wt.%. The average activity coefficients obtained are γNio = 2.70 ± 0.52 (77 experiments), γcoo = 1.51 ± 0.28 (76 exp.) and γ“Feo” = 1.70 ± 0.22 (57 exp.) relative to the respective pure liquid oxide standard states and simple'oxide mole fractions.